2010
DOI: 10.1371/journal.pone.0009748
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Deletion of Smyd2 Is Dispensable for Mouse Heart Development

Abstract: Chromatin modifying enzymes play a critical role in cardiac differentiation. Previously, it has been shown that the targeted deletion of the histone methyltransferase, Smyd1, the founding member of the SET and MYND domain containing (Smyd) family, interferes with cardiomyocyte maturation and proper formation of the right heart ventricle. The highly related paralogue, Smyd2 is a histone 3 lysine 4- and lysine 36-specific methyltransferase expressed in heart and brain. Here, we report that Smyd2 is differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 62 publications
(75 reference statements)
4
77
0
Order By: Relevance
“…Intriguingly, it was recently reported that smyd2a knockdown generates severe skeletal and cardiac muscle defects in zebrafish (Donlin et al, 2012, Voelkel et al, 2012. Regarding the cardiac phenotype, we did not appreciate any abnormalities, even in the very severe morphant phenotype at 6 dpf, consistent with mice conditional-knockout experiments where Smyd2 was dispensable for heart development (Diehl et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Intriguingly, it was recently reported that smyd2a knockdown generates severe skeletal and cardiac muscle defects in zebrafish (Donlin et al, 2012, Voelkel et al, 2012. Regarding the cardiac phenotype, we did not appreciate any abnormalities, even in the very severe morphant phenotype at 6 dpf, consistent with mice conditional-knockout experiments where Smyd2 was dispensable for heart development (Diehl et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Unexpectedly, adult hearts of Smyd2 conditional knockout mice showed no changes in p21 and mdm2 expression levels, and had no global effect in H3K36 or H3K4 methylation (Diehl et al, 2010). Additionally, Smyd2 was found dispensable for proper heart development in mouse (Diehl et al, 2010). Rb protein can be methylated by SMYD2 at K860 and facilitates its interaction with the methyl-binding protein L3MBTL1 (Saddic et al, 2010).…”
Section: Smyd2 Expression Is Strongly Induced During Human Es Cell DImentioning
confidence: 97%
See 1 more Smart Citation
“…SMYD2 plays an important role in embryonic stem cell biology and skeletal and cardiac muscle function but is dispensable for heart development (Diehl et al 2010;Donlin et al 2012;Sese et al 2013;Sajjad et al 2014). Beyond these activities, normal physiological roles for SMYD2 in vivo remain largely unknown.…”
Section: Smyd2 Is Required For Efficient Pdac Development In Micementioning
confidence: 99%
“…In zebrafish, knockdown of the zebrafish SMYD1 isoforms, SMYD1a and SMYD1b by morpholino-modified antisense oligonucleotides leads to impaired heart and skeletal muscle function due to disturbed myofibril organization . SMYD2, although highly expressed in cardiomyocytes, was recently found to be dispensable for cardiac development because cardiac-specific deletion of SMYD2 in mice does not interfere with normal heart morphogenesis and function (Diehl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%